2014
DOI: 10.1128/aac.02495-13
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of BMS-791325, an Allosteric Inhibitor of Hepatitis C Virus NS5B Polymerase

Abstract: BMS-791325 is an allosteric inhibitor that binds to thumb site 1 of the hepatitis C virus (HCV) NS5B RNA-dependent RNA polymerase. BMS-791325 inhibits recombinant NS5B proteins from HCV genotypes 1, 3, 4, and 5 at 50% inhibitory concentrations (IC 50 ) below 28 nM. In cell culture, BMS-791325 inhibited replication of HCV subgenomic replicons representing genotypes 1a and 1b at 50% effective concentrations (EC 50 s) of 3 nM and 6 nM, respectively, with similar (3 to 18 nM) values for genotypes 3a, 4a, and 5a. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 56 publications
3
49
0
Order By: Relevance
“…Thus, we expect the impact on authentic gt 3a virus to be similar to the impact on the hybrid virus used in the experiment (33,34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we expect the impact on authentic gt 3a virus to be similar to the impact on the hybrid virus used in the experiment (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…NS3 protease inhibitors bind the catalytic site or the NS4A activator site, defining 2 targets that inactivate protease function to inhibit replication (47). NS5B inhibitors bind to 1 of 4 allosteric inhibitor binding sites or the catalytic site, defining 5 targets that inactivate the polymerase to inhibit virus replication (33,48,49). Displacement of bound radiolabeled compound suggests the less wellcharacterized inhibitors of NS4B bind at least one site that inhibits replication (50).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the P495L variant is ϳ2-fold lower than WT and is highly resistant to BMS-791325 inhibition (EC 50 Ͼ500 nM and IC 50 431 Ϯ 110 nM; Table 2) (10, 11). It was observed in replicons after selection in vitro and in clinical specimens of GT-1 patients treated with BMS-791325 (7,11). The P495L and L30S variants were used in this study to confirm that the inhibition and binding observed with WT NS5B is specific and to probe the impact of the weakened interaction between the thumb and finger on the inhibitor-enzyme interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent Phase 2 study, 63 of 66 HCV-infected GT-1 patients treated for 12 or 24 weeks with a combination of BMS-791325 (75 or 150 mg twice daily), daclatasvir (60 mg once daily), and asunaprevir (200 mg twice daily) achieved sustained virologic response (9). The preclinical profile of BMS-791325, including potent activity in GT-1a and -1b enzyme and replicon assays (IC 50 and EC 50 values of 0.7-4 nM), selection of significant resistance at a single substitution site, and a robust pharmacokinetic profile in animal models, anticipated the strong antiviral effect observed in patients (10,11).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 1 more Smart Citation